Sosialisasi Tentang Investasi Untuk Warga Kembangan Utara Jakarta Barat - Swarmilah Hariani; Harnovinsah Harnovinsah; Venny Venny (LPMP Imperium, 2019)
This community service activity is themed “Information about the Capital Market to North Kembangan residents in West Jakarta